Development of dense solid state thin-film electrolyte for fluoride ion batteries - Anji Munnangi (Journal of Alloys and Compounds, 2016)
Dense thin-film electrolyte of La0.9Ba0.1F2.9 has been fabricated on stainless steel substrates by spin coating of a complex and sintering. The resulting layers had a thickness of 4–5 μm. The effect of sintering temperature (400, 450 and 500 °C) and time (0.5, 2 and 4 h) was studied in order to control the morphology and the ionic conductivity of the films. The composition and morphology of the fabricated films were characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM). Tysonite type structure was retained when the films were sintered at 450 °C or below while an impurity of LaOF was formed when the films were sintered at 500 °C. SEM results indicate that higher temperature and longer time of sintering resulted in dense films. Ionic conductivities of the fabricated films were determined by electrochemical impedance spectroscopy (EIS). The thin films sintered at 450 °C for 4 h exhibited high ionic conductivity of 1.6 × 10−4 S cm−1 at 170 °C. The optimal preparation condition of La0.9Ba0.1F2.9 films was sintering at 450 °C for 4 h.